2022
DOI: 10.1177/09544062221075943
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Boltzmann modeling of plasma shock wave

Abstract: Plasma shock waves widely exist and play an important role in high-energy-density environment, especially in the inertial confinement fusion. Due to the large gradient of macroscopic physical quantities and the coupled thermal, electrical, magnetic, and optical phenomena, there exist not only hydrodynamic non-equilibrium (HNE) effects but also strong thermodynamic non-equilibrium (TNE) effects around the wavefront. In this work, a two-dimensional single-fluid discrete Boltzmann model is proposed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In recent years, the kinetic methods based on the Boltzmann equation have become a popular mesoscopic simulation approach in various fields [20][21][22][23]. In particular, the discrete Boltzmann method (DBM) [24,25] is suitable for supersonic waves with essential nonequilibrium effects, such as the steady or unsteady detonation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the kinetic methods based on the Boltzmann equation have become a popular mesoscopic simulation approach in various fields [20][21][22][23]. In particular, the discrete Boltzmann method (DBM) [24,25] is suitable for supersonic waves with essential nonequilibrium effects, such as the steady or unsteady detonation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that the DBM offers a novel systematic scheme and a set of convenient and efficient tools for describing, measuring and analysing simultaneously THNE effects that cannot be described adequately by traditional hydrodynamic models (Xu et al 2012;Gan et al 2015Gan et al , 2018Lai et al 2016;Zhang et al 2019Zhang et al , 2021Zhang et al , 2022aChen et al 2020Chen et al , 2022aLiu et al 2022). The DBM was developed from a branch of the LBM that aims to describe the non-equilibrium flows from a more fundamental level and is no longer based on the simple 'propagation + collision' lattice gas evolution scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic features, such as the unbalancing and mutual conversion of internal energy at different degrees of freedom, provide appropriate criteria for determining whether or not higher-order TNE effects should be considered in the modelling, and which level of DBM should be adopted (Lin et al 2014;Gan et al 2015Gan et al , 2018. In plasma physics, kinetic features have been used to distinguish plasma shock wave from shock wave in ordinary neutral flow (Liu et al 2022). These findings and observations shed light on the fundamental mechanisms of various compressible flow systems.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete Boltzmann method (DBM) is a modeling and analysis method based on kinetic theory in statistical physics [73][74][75][76][77][78][79][80] . It provides various measures to detect, describe and exhibit the complex Thermodynamic Non-Equilibrium (TNE) behaviors, and has brought a series of new insights in several fields in recent years, such as multiphase flow [81][82][83][84][85] , rarefied gas flow 86,87 , combustion and detonation [88][89][90][91][92][93][94][95][96][97] , hydrodynamic instabilities [98][99][100][101][102][103][104][105] , etc.…”
Section: Introductionmentioning
confidence: 99%